Three-year monitoring results of nitrate and ammonium wet deposition in Thailand - Suparb Paramee (2018)
Wet deposition is one of the important sources of nitrogen input into the ecosystem. It also contributes to rain acidity in some environments. In this study we reported the annual as well as seasonal trends of nitrogen wet deposition at three locations in Thailand: Bangkok, Chiang Mai and Nan. Comparison of nitrogen wet deposition between in rural and in the urban areas was also made. Daily rainfall was measured and monthly rainwater was collected for nitrogen analysis during 1999-2002. The average NO3-concentration in rainwater collected from the rural sites (60 km from urban area) was around 0.2-0.3 mg L-1, while that from the urban areas of Chiang Mai and Nan cities it was 0.4-0.5 mg L-1. NH4+concentration in rainwater showed the similar ranges to that of NO3-, except at Nan where concentration was not significantly different between the urban and rural sites. On the other hand, the average concentrations of NO3-were higher at Bangkok site than other sites, while concentration of NH4+was almost the same between Chiang Mai and Bangkok. Wet deposition of NO3-at the rural sites of Chiang Mai and Nan ranged from 2.1 to 3.2 kg N ha-1yr-1, while at the urban sites this ranged from about 6 kg N ha-1yr-1in Chiang Mai and Nan Cities to 8.6 kg N ha-1yr-1in Bangkok. Wet deposition of NH4+at the rural sites of Chiang Mai and Nan was about 2.4 to 3.6 kg N ha-1yr-1and at the urban sites of Chiang Mai, Nan and Bangkok this was 7.7, 4.9 and 8.1 kg N ha-1yr-1, respectively. Thus, it was concluded that wet deposition of both nitrogen species was significantly higher at the urban sites than at the rural sites. © Springer Science + Business Media, Inc. 2005.